1989
DOI: 10.1111/j.1365-2133.1989.tb08218.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulphamethoxypyridazine for dermatitis herpetiformis, linear IgA disease and cicatricial pemphigoid

Abstract: One-hundred and sixty-eight cases of dermatitis herpetiformis were reviewed to compare the clinical response to and incidence of side-effects from dapsone and sulphamethoxypyridazine. Thirty-seven received sulphamethoxypyridazine (0.25-1.5 g/day) as a single agent therapy at some stage during their care and 161 had dapsone only (50-450 mg/day). Thirty of these patients received both drugs, but at different times. Both were highly effective in controlling the skin disease in 97% of patients on dapsone and 89% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 6 publications
0
35
0
2
Order By: Relevance
“…Monitoring for potential side effects is critical given the risk of hemolytic anemia, methemoglobinemia, neuropathy, and hypersensitivity (discussed in more detail previously in the section describing the use of dapsone in the treatment of BP). Sulfasalazine and sulfamethoxypyridazine can be useful in patients who cannot tolerate dapsone or when dapsone is ineffective 98,99 ; however, the mainstay of therapy is initiation of a gluten-free diet, as this reduces the need for medication, resolves underlying enteropathy, and reduces the risk of lymphoma in these patients. 100 Patients should be referred to a dietician for guidance on adhering to a gluten-free diet, as many food ingredients contain gluten.…”
Section: Dermatitis Herpetiformismentioning
confidence: 99%
“…Monitoring for potential side effects is critical given the risk of hemolytic anemia, methemoglobinemia, neuropathy, and hypersensitivity (discussed in more detail previously in the section describing the use of dapsone in the treatment of BP). Sulfasalazine and sulfamethoxypyridazine can be useful in patients who cannot tolerate dapsone or when dapsone is ineffective 98,99 ; however, the mainstay of therapy is initiation of a gluten-free diet, as this reduces the need for medication, resolves underlying enteropathy, and reduces the risk of lymphoma in these patients. 100 Patients should be referred to a dietician for guidance on adhering to a gluten-free diet, as many food ingredients contain gluten.…”
Section: Dermatitis Herpetiformismentioning
confidence: 99%
“…SMXP has been shown to be effective in dermatitis herpetiformis, linear IgA disease, and cicatricial pemphigoid. 15 McFadden et al 15 achieved control of symptoms and rash in 32 out of 37 patients with dermatitis herpetiformis using 0.25 g to 1.5 g SMXP daily. More recently SMXP was reported as a successful treatment of mucous membrane pemphigoid.…”
Section: Discussionmentioning
confidence: 97%
“…(1,2,7) Sulfamethoxypyridazine (0.5-1.5g/day) is also an effective treatment in children as it causes less hemolysis. (8) Recent trials have shown complete remission by flucoxacillin within 3 to 4 months from starting the therapy. Reports have also shown the benefit of colchicines (0.5-2mg/day), cyclosporine, tetracycline, nicotinamide, mycophenolate and erthyromycin to be effective.…”
Section: Discussion: By Definition Linearmentioning
confidence: 99%